2007
DOI: 10.1007/s10682-007-9186-4
|View full text |Cite
|
Sign up to set email alerts
|

MHC-associated mating strategies and the importance of overall genetic diversity in an obligate pair-living primate

Abstract: Mate choice is one of the most important evolutionary mechanisms. Females can improve their fitness by selectively mating with certain males. We studied possible genetic benefits in the obligate pair-living fat-tailed dwarf lemur (Cheirogaleus medius) which maintains life-long pair bonds but has an extremely high rate of extra-pair paternity. Possible mechanisms of female mate choice were investigated by analyzing overall genetic variability (neutral microsatellite marker) as well as a marker of adaptive signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 110 publications
(127 reference statements)
5
67
0
Order By: Relevance
“…For example, Banks et al [55] described a positive correlation between heterozygosity at MHC-linked markers and survival in a long-lived mammal species (the mountain brushtail possum Trichosurus cunninghami). In males of fat-tailed dwarf lemur (Cheirogaleus medius) and grey mouse lemur (Microcebus murinus), MHC individual allelic diversity was associated with increased reproductive success [56]. Worley et al [20] observed a higher survival rate of MHC heterozygous individuals in red junglefowl (Gallus gallus) and also identified a particular MHC genotype strongly affecting survival probabilities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Banks et al [55] described a positive correlation between heterozygosity at MHC-linked markers and survival in a long-lived mammal species (the mountain brushtail possum Trichosurus cunninghami). In males of fat-tailed dwarf lemur (Cheirogaleus medius) and grey mouse lemur (Microcebus murinus), MHC individual allelic diversity was associated with increased reproductive success [56]. Worley et al [20] observed a higher survival rate of MHC heterozygous individuals in red junglefowl (Gallus gallus) and also identified a particular MHC genotype strongly affecting survival probabilities.…”
Section: Discussionmentioning
confidence: 99%
“…MHC-disassortative mating occurs across fish, reptiles, birds, and mammals (Milinski, 2006;Penn, 2002;Roberts, 2009;Setchell & Huchard, 2010). In some socially monogamous birds and mammals (including primates), females not only choose to pair with MHC-dissimilar mates but are also more likely to engage in extra-pair copulations (evidenced by mixed paternity clutches) if their mate is relatively MHC-similar (FreemanGallant, Wheelwright, Meiklejohn, & Sollecito, 2006;Schwensow, Fietz, Dausmann, & Sommer, 2008); in so doing, they gain further genetic diversity in their offspring, with associated benefits in offspring health and survival (Foerster, Delhey, Johnsen, Lifjeld, & Kempenaers, 2003;Petrie & Kempenaers, 1998).…”
Section: Mhc-correlated Partner Preferencementioning
confidence: 99%
“…Although most studies have focused on morphological and behavioural traits [1], evidence is accruing for multiple genetic criteria for mate choice [2,3]. Females may choose males with 'good genes', such as those with alleles or allele combinations increasing fitness [4,5] or with high heterozygosity [6][7][8].…”
Section: Introductionmentioning
confidence: 99%